Densification of MnSO4 ceramics by Cool-SPS: Evidences for a complex sintering mechanism and magnetoelectric coupling. Issue 11 (September 2018) - Hérisson de Beauvoir, T.; Molinari, F.; Chung-Seu, U.C.; Michau, D.; Denux, D.; Josse, M.
Graphical abstract: Abstract: Dense ceramics of MnSO4 composition have been successfully densified at 400 °C in only 5 min under a uniaxial pressure of 400 MPa, using Spark Plasma Sintering technique. Since the stable form of MnSO4 in ambient atmosphere is its hydrate MnSO4 ·H2 O, crystallizing in a different space group, dehydration is required to reach a purely anhydrous phase. In situ dehydration during Spark Plasma Sintering allows to lower both sintering temperature and time. Applied pressure strongly influences dehydration step and therefore is a key parameter to tune densification, so far as to obtain a dense MnSO4 ·H2 O ceramic. The presence of a reversible phase transition to a β-MnSO4 high temperature form seems to influence the dehydration temperature under pressure, and likely drives the sintering mechanisms. The high densification obtained, beyond 95% of theoretical density, added to the preservation of the structural and physical properties of MnSO4 after sintering allowed to perform reliable and reproducible measurements showing a dielectric anomaly associated to the magnetic transition, and the hysteretic behaviour of capacitance versus magnetic field, which is a clue for an intrinsic magnetoelectric coupling in MnSO4 .